Advanced SDOF Model for Steel Members Subject to Explosion Loading: Material Rate Sensitivity: (FABIG Technical Note 10) (Steel Construction Institute (SCI), 2002)
This Technical Note describes an extension to a sophisticated single-degree-of-freedom (SDOF) model for steel members subject to explosion loading. The SDOF model in this document extends the SDOF model previously developed in FABIG Technical Note 7 to include strain rate effects and to provide more rational ductility measures than those based on the rate-insensitive model. The Technical Note proceeds by providing an overview of the problem characteristics as well as the formulation method used in developing the new SDOF model, where consideration is given to material rate sensitivity in accordance with the Cowper-Symonds model.